Lysine methyltransferase 2D regulates pancreatic carcinogenesis through metabolic reprogramming. Issue 7 (18th October 2018) - Koutsioumpa, Marina; Hatziapostolou, Maria; Polytarchou, Christos; Tolosa, Ezequiel J; Almada, Luciana L; Mahurkar-Joshi, Swapna; Williams, Jennifer; Tirado-Rodriguez, Ana Belen; Huerta-Yepez, Sara; Karavias, Dimitrios; Kourea, Helen; Poultsides, George A; et al.
Abstract : Objective: Despite advances in the identification of epigenetic alterations in pancreatic cancer, their biological roles in the pathobiology of this dismal neoplasm remain elusive. Here, we aimed to characterise the functional significance of histone lysine methyltransferases (KMTs) and demethylases (KDMs) in pancreatic tumourigenesis. Design: DNA methylation sequencing and gene expression microarrays were employed to investigate CpG methylation and expression patterns of KMTs and KDMs in pancreatic cancer tissues versus normal tissues. Gene expression was assessed in five cohorts of patients by reverse transcription quantitative-PCR. Molecular analysis and functional assays were conducted in genetically modified cell lines. Cellular metabolic rates were measured using an XF24-3 Analyzer, while quantitative evaluation of lipids was performed by liquid chromatography-mass spectrometry (LC-MS) analysis. Subcutaneous xenograft mouse models were used to evaluate pancreatic tumour growth in vivo. Results: We define a new antitumorous function of the histone lysine (K)-specific methyltransferase 2D (KMT2D) in pancreatic cancer. KMT2D is transcriptionally repressed in human pancreatic tumours through DNA methylation. Clinically, lower levels of this methyltransferase associate with poor prognosis and significant weight alterations. RNAi-based genetic inactivation of KMT2D promotes tumour growth and results in loss of H3K4me3 mark. In addition, KMT2D inhibition increases aerobic glycolysis and alters the lipidomic profiles of pancreatic cancer cells. Further analysis of this phenomenon identified the glucose transporter SLC2A3 as a mediator of KMT2D-induced changes in cellular, metabolic and proliferative rates. Conclusion: Together our findings define a new tumour suppressor function of KMT2D through the regulation of glucose/fatty acid metabolism in pancreatic cancer.